2018
DOI: 10.1016/j.java.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A Bundled Approach to Decrease the Rate of Primary Bloodstream Infections Related to Peripheral Intravenous Catheters

Abstract: Background: Peripheral intravenous catheters (PIVs) have been considered as having lower risk of infection than central lines. However, research is limited regarding numbers of primary bloodstream infections related to peripheral lines and prevention of peripheral line-associated bloodstream infections (PLABSI). Methods: Our aim was to create and monitor compliance with a new PIV maintenance bundle using disinfecting caps and tips and to assess whether this bundle would lead to a decrease in PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…All included studies reported implementing a PIVC care bundle for insertion (n Z 9) or maintenance (n Z 10), or both (n Z 8) in an acute care hospital inpatient setting. Studies were conducted in a range of countries, including Australia [32,36], USA [25,26,29], UK [27], Spain [30,33], Germany [34], Taiwan [24], South Korea [31], and Thailand [35]. Bundles were implemented for the adult (n Z 10), paediatric (n Z 2), and neonate (n Z 1) populations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All included studies reported implementing a PIVC care bundle for insertion (n Z 9) or maintenance (n Z 10), or both (n Z 8) in an acute care hospital inpatient setting. Studies were conducted in a range of countries, including Australia [32,36], USA [25,26,29], UK [27], Spain [30,33], Germany [34], Taiwan [24], South Korea [31], and Thailand [35]. Bundles were implemented for the adult (n Z 10), paediatric (n Z 2), and neonate (n Z 1) populations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This unit collects patient data from hospitals locally or remotely from the portal's website and by using laptops, the Internet, hospital databases, and scanners. Table illustrates a part of the injury model in the primary bloodstream and completion instructions (Duncan, Warden, Bernatchez, & Morse, ). To determine whether a patient has CLABSI infection, further data and symptom criteria should be used, as explained in the next sections.…”
Section: System Proposed Methodology and Algorithmsmentioning
confidence: 99%
“…A positive blood culture with ciphers and symptoms of infection is evidence of blood infection. The patient may develop HAI‐CLABSI status if patient suffers from fever or chills, or skin around the catheter becomes sore and red; when the BSI arises and there is no other possible source of this infection; infection is related to the central line; and the infection is possibly from an alternative source, but the source is obscure (Duncan et al, ). …”
Section: System Proposed Methodology and Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations